Saensaeb Canal : History and Development - Chiwachaisak, Waraporn (Journal of Thai Studies, 2023)
This research aims at studying the history of Saensaeb Canal, the first canal to be dug in the reign of King Rama III. The study focuses on the importance of the canal and the environmental, physical, social and cultural changes which have affected the role of the canal and the cultural dimension of the communities along the canal. The research found that the need to carry military supplies during the long-lasting war between Thailand and Vietnam during the reign of King Rama III of the Rattanakosin period was the main reason for digging the Saensaeb Canal. After the war, the canal became a waterway artery on the east side of the Chao Phraya River when the city was extended along the canal. The importance of the Saensaeb Canal increased after the signing of the Burney and Bowring Treaties when there was an increase in local and international trade in Thailand. Also, plantations, especially rice and sugar cane, were expanded for exports. The land on the banks of the Saensaeb Canal was used for agricultural purposes, worked by a large number of war captives who were Lao, Malay, Mon, Khmer, as well as by Chinese laborers who had settled in Thailand. These ethnic groups lived in their own communities, freely led their traditional ways of life, and peacefully co-existed along the canal. As time went by, the Saensaeb Canal was developed and improved. The government provided appropriate administration for the people on both sides of the canal. To date, there are 18 districts under the Bangkok Metropolitan Administration along the canal. The Saensaeb Canal, which was dug almost 200 years ago, is one of the most important canals in the history of Thailand, although it is no longer one of the main waterways. However, the Saensaeb Canal is an alternative traff ic route for people in Bangkok and its suburbs and an interesting canal with a diverse cultural heritage.